Questioning the Criteria for Evaluating Non-Cryptographic Hash Functions. - Hayes, Catherine; Malone, David (Communications of the ACM, 2025)
This article examines the criteria used to evaluate non-cryptographic hash functions, which prioritize speed and efficiency over security. While these functions aim to uniformly distribute inputs across resources, challenges such as input patterns, modulo bias, and limitations in uniformity remain. Traditional measures like the avalanche criterion may not fully address real-world needs, as they focus more on randomizing input-output relationships than practical distribution in hash tables. The discussion highlights the need for tailored approaches to hash function design, balancing efficiency with application-specific requirements, and questions the feasibility of a one-size-fits-all solution.